1991
DOI: 10.1111/j.1469-7610.1991.tb01923.x
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of the Role of Ethnicity in Children's Social Perception

Abstract: This study examines the salience of ethnicity in 8- and 11-year-old children's social categorizations and preference judgements. Unlike previous research, children were afforded the possibility of responding to photographs of target persons on the basis of either individual characteristics (expressed affect) or group characteristics (ethnicity and gender), and it was found that ethnicity was seldom used as a basis for categorizing persons, nor was it widely implicated in judgements of preference. Since this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
3
11
1
Order By: Relevance
“…The same pattern of results for the use of racial and other features appeared. Hence, no confirmation was found for the prediction that members of minority groups will pay more attention to racial cues than majority members, which is also found in other studies (Bennett et al, 1991;Verkuyten and Masson, 1994). One reason might be that in most studies, including the present one, all subjects live in the same neighbourhoods and schools.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The same pattern of results for the use of racial and other features appeared. Hence, no confirmation was found for the prediction that members of minority groups will pay more attention to racial cues than majority members, which is also found in other studies (Bennett et al, 1991;Verkuyten and Masson, 1994). One reason might be that in most studies, including the present one, all subjects live in the same neighbourhoods and schools.…”
Section: Discussioncontrasting
confidence: 76%
“…Other studies also show that children use facial cues indicating positive or negative affect and in general that children often mention small details that do not relate to race (Aboud, 1988). For instance, Bennett, Dewberry and Yeeles (1991) found that race was seldom used as a basis for categorizing photographs whereas references to gender were frequent. Additionally, they found to their surprise that the 8-year-old's used type of seat as a feature for categorizing.…”
Section: Introductionmentioning
confidence: 99%
“…By pre‐adolescence, children are less likely to rely solely on these global categories to classify people. Instead, they are more likely to categorize people at the subgroup level and/or along multiple categories simultaneously (Verkuyten, Masson, & Elffers, 1995), or rely on individuating information such as facial expressions (Bennett, Dewberry, & Yeeles, 1991; Katz, Sohn, & Zalk, 1975). When pre‐adolescent children are given explicit directions to sort pictures into two groups or groups of equal amounts, ethnicity seems to be more salient than gender, age, clothing style or facial expression (Davey & Norburn, 1980; Verkuyten et al , 1995).…”
Section: Developmental Trends In Categorization Of Social Targetsmentioning
confidence: 99%
“…For example, gender (Verkuyten, Masson, & Elffers, 1995;Yee & Brown, 1988), ethnicity (Davey & Norburn, 1980;Verkuyten et al, 1995) and age (Yee & Brown, 1988) all appear to be important in children's social categorization. Children, like adults, have also been found to distinguish others on the basis of body-type (Powlishta, Serbin, Doyle, & White, 1994), whether or not they are able-bodied (Maras, 1993), and with respect to personal attributes (Bennett, Dewberry, & Yeeles, 1991). This research has typically relied on methods which involve presenting children with stimuli, such as photographs representing members of different social categories, and requiring that they sort them into what they take to be homogeneous groupings.…”
mentioning
confidence: 99%